Heart transplantation in secondary dilated cardiomyopathy due to myocarditis. Case report - D. V. Romashova; N. Z. Madatov; O. K. Yakovitskaya (Кардиоваскулярная терапия и профилактика)
Heart failure (HF) is a prognostically unfavorable complication of cardiovascular diseases. The presented case report describes the management of a patient with severe progressive biventricular HF due to myocarditis, refractory to therapy and requiring heart transplantation. Issues of timely diagnosis of HF and the feasibility of radical surgical treatment are discussed.